2006
DOI: 10.1093/hmg/ddl204
|View full text |Cite
|
Sign up to set email alerts
|

TBC1D1 is a candidate for a severe obesity gene and evidence for a gene/gene interaction in obesity predisposition

Abstract: The molecular etiology of obesity predisposition is largely unknown. Here, we present evidence that genetic variation in TBC1D1 confers risk for severe obesity in females. We identified a coding variant (R125W) in TBC1D1 that segregated with the disease in 4p15-14-linked obesity pedigrees. In cases derived from pedigrees with the strongest linkage evidence, the variant was significantly associated with obesity (P=0.000007) and chromosomes carrying R125W accounted for the majority of the evidence that originall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
128
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(135 citation statements)
references
References 44 publications
4
128
3
Order By: Relevance
“…34 Recently, a novel obesity linkage region was discovered by conditioning analysis on a SNP in TBC1D1, itself recently linked to obesity in the same pedigrees. 35 However, none of these conditional linkage analyses have led to a gene discovery. The HTR1A-conditional linkage of LHPP to MDD is the first for which a linked gene in an interacting region has been identified, and the first for which the gene-gene interaction has been further supported by showing conditional association in population studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Recently, a novel obesity linkage region was discovered by conditioning analysis on a SNP in TBC1D1, itself recently linked to obesity in the same pedigrees. 35 However, none of these conditional linkage analyses have led to a gene discovery. The HTR1A-conditional linkage of LHPP to MDD is the first for which a linked gene in an interacting region has been identified, and the first for which the gene-gene interaction has been further supported by showing conditional association in population studies.…”
Section: Discussionmentioning
confidence: 99%
“…These transcripts are shown in Figure 4. Expression levels were categorized according to threshold cycle: very high ( < 20), high (20)(21)(22)(23)(24)(25), moderate (25)(26)(27)(28)(29)(30), low (30)(31)(32)(33)(34)(35), very low/questionable (35)(36)(37)(38)(39)(40) or not detected (no signal above background after 40 cycles). Because of the linkage and association of LHPP variants to MDD, there was particular focus on measuring expression of these transcripts in the brain (Figure 3b).…”
Section: Serotonin Receptor 1a-conditional Genetic Analysismentioning
confidence: 99%
“…Tbc1d1, a critical protein associated with human obesity (19,25), was drastically reduced in the Tardbp deleted iTDPKO cells (−7.35 fold, P = 7.02E−228). As it has been reported that a nonfunctional Tbc1d1mutant in the skeletal muscle is responsible for the lean phenotype in mice and thatTbc1d1is essential for Glut4 translocation to the plasma membrane of skeletal muscle cells for glucose uptake (18), a decrease inTbc1d1 in skeletal muscle might offer an explanation for the lean phenotype shown in our conditional Tardp-KO mouse model (Fig.…”
Section: Marked Fat Loss and High Fatty Acid Consumption In Conditionalmentioning
confidence: 99%
“…The potential importance of Tbc1d1 in linking insulin, exercise and energy status signalling with GLUT4 membrane traffic is heightened by the additional recent discovery by Stone et al [13]. This group has reported that the gene coding for Tbc1d1 is a candidate severe obesity gene [13].…”
mentioning
confidence: 99%
“…This group has reported that the gene coding for Tbc1d1 is a candidate severe obesity gene [13]. A defect in this gene (leading to substitution of tryptophan for arginine) is present in some cases of severe obesity in females and gene-gene interaction studies have provided evidence that Tbc1d1 may give rise to obesity predisposition.…”
mentioning
confidence: 99%